"I am like a deaf, dumb and blind person": Mobility and immobility of Chinese (im)migrants in Flushing, Queens, New York City. (June 2016) - Yu, Shaolu
Abstract: This paper contributes to research on daily mobility experience of (im)migrants in cities and expands the conceptualizations of mobility by examining intentionality and its relations to locality. Through place-based research on mobility and immobility of Chinese (im)migrants in Flushing, Queens, New York City, this paper explores: 1) mobility patterns of recent (im)migrants in an urban setting; 2) the constraints, resources and their coping strategies for everyday mobility; and 3) the dialectal relationship between voluntary and involuntary immobility, and between mobility and ethnic communities. This study reveals that immobility is not always the result of inaccessibility, but structural barriers in the broader society such as socioeconomic inequality and racial discrimination. Involuntary immobility encourages overdependence on locality. With its high place accessibility, Flushing provides (im)migrants with a plethora of ethnic mobile resources, as well as social networks and community resources. The relative immobility among Chinese (im)migrants in Flushing is compensated by the flows and movements of people, goods and information both at the local and transnational scale. The contrast between insider-ness and outsider-ness further enhances their attachment to the local community and discourages them from moving. Thus, locality mitigates involuntary immobility but paradoxically nurtures voluntary immobility that hinders the transfer of potential mobility to actual mobility, and physical mobility to social mobility. Without considering locality, stillness is easily mistaken for immobility; without considering intentionality, accessibility is easily equated to mobility. Therefore, solutions to transportation equity do not lie solely in transportation accessibility itself, but more broadly in individual capability, immigration policy, labor market equality and community development. Highlight: Everyday mobility patterns among recent Chinese (im)migrants in Flushing, NYC Intentionality determines the difference between mobility and accessibility. The interrelationships between place and mobility Transportation equity lies broadly in immigration policy and community development.